2019
DOI: 10.1111/joor.12905
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between conventional and computerised methods in the assessment of an occlusal scheme

Abstract: The paradigm about the ideal dental occlusion schemes in rehabilitation procedures has changed over time. [1][2][3] Indeed, based on suggestions that the role of dental occlusion features is less important than believed in the past in the aetiology of temporomandibular disorders (TMD), bruxism or functional impairment, very basic occlusal schemes are enough to maintain the homeostasis of the stomatognathic system. [3][4][5][6] Nonetheless, this does not mean that occlusion evaluations and adjustments should no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…In a recent study, Diaz et al 33 assessed the correlation between the conventional, photographic and computerized occlusal evaluation methods in the clinical settings and concluded that none of the three could actually be considered the standard of reference. In the present study, extraoral photography was chosen for quantitative analysis of the occlusal marks using an analysis software, as it has been demonstrated to be more objective compared to the visual interpretation of the clinicians 33 . Furthermore, the different thickness of the foils used in the two papers could have affected the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, Diaz et al 33 assessed the correlation between the conventional, photographic and computerized occlusal evaluation methods in the clinical settings and concluded that none of the three could actually be considered the standard of reference. In the present study, extraoral photography was chosen for quantitative analysis of the occlusal marks using an analysis software, as it has been demonstrated to be more objective compared to the visual interpretation of the clinicians 33 . Furthermore, the different thickness of the foils used in the two papers could have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Zhang et al, 16 photographs to rate the occlusal contacts were taken by two independent clinicians, T‐Scan was utilized to observe occlusion with dynamic quantitative analysis, and the muscle activity was evaluated by means of EMG examinations. In a recent study, Diaz et al 33 assessed the correlation between the conventional, photographic and computerized occlusal evaluation methods in the clinical settings and concluded that none of the three could actually be considered the standard of reference. In the present study, extraoral photography was chosen for quantitative analysis of the occlusal marks using an analysis software, as it has been demonstrated to be more objective compared to the visual interpretation of the clinicians 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the measurement of occlusal contact points, the commonly used traditional clinical methods include the occlusal paper method, the occlusal wax chip method and the silicone rubber method. Although these methods have a certain rationality, they are easily influenced by subjective or objective conditions 5 . With the introduction of digital technologies into the field of dentistry, such as the T‐scan system and the iTero scanner, the study of occlusal analysis has gradually been quantified, and the description of occlusal contact has evolved from static to dynamic recording.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods have a certain rationality, they are easily influenced by subjective or objective conditions. 5 With the introduction of digital technologies into the field of dentistry, such as the T-scan system and the iTero scanner, the study of occlusal analysis has gradually been quantified, and the description of occlusal contact has evolved from static to dynamic recording. The T-scan system can be used to record and analyse the force and timing of occlusal contact and the correspondence between them.…”
Section: Introductionmentioning
confidence: 99%